THE INFLUENCE OF LINGUISTIC TOWARD ENGLISH ACHIEVEMENT AT SMA TUGU IBU, DEPOK - Mu'thia Mubasyira; Noni Marlianingsih; Dewi Mutiara Indah Ayu (Deiksis, 2015)
The aim of this research is to know the influence of linguistic intelligence towards English achievement at SMA Tugu Ibu in Depok. The data for linguistic intelligence is taken from worksheet though test. Meanwhile the data for English achievement is taken from the score of English in students’ academic record which is familiar called rapor. To analyze the data, the researcher uses SPSS (Statistical Product and Service Solution) version 17. Based on the result of the data analysis, it is known that coefficient correlation (r) = 0,766 and determination coefficient is 58,7%. It means that there are significant and strong influence of linguistic intelligence towards English achievement. It means that there are significant and strong influence of linguistic intelligence towards English achievement. English is influenced by linguistic intelligence for 58,7%. Meanwhile, the rest 41,3% is influenced by other factors. Futhermore, the test of hypotheses through regression analysis make the result for regression equality Y = 55,48 + 1,747 X. the result for regression equality significant test is got the score of Sig = 0,000 and tobserved = 6,307 so Sig score < 0,05 And tobserved > ttable so Ho is rejected and H1 is accepted. It means that regression coefficient is significant. The conclusion is there are strong and significant influence of linguistic intelligence towards English achievement at SMA Tugu Ibu in Depok, West Java.Keywords : Linguistic Intelligence and English Achievement.